Determinasi Faktor Finansial dan Non Finansial Terhadap Opini Audit Going Concern - Edison Fernandus, (2022)
This study is a quantitative study conducted to examine Liquidity, Cash Flow Ratio, Efficiency Ratio, Public Accounting Firm Reputation, Covid-19 Explanatory Notes, and previous year's audit opinion which were used as control variables. The population in this research are tourism, restaurant & hotel sector companies and transportation & logistics sector companies listed on the Indonesia Stock Exchange in 2018-2020. The sampling technique used purposive random sampling with 53 companies that have met the sampling criteria. Hypothesis testing with logistic regression analysis through the SPSS (Statistical Product and Service Solution) version 26 program with a significance level of 5% (0.05). The results of this study indicate that the Covid-19 Explanatory Notes have a significant positive effect on going concern audit opinions, while liquidity, cash flow ratios, efficiency ratios, and KAP reputation have no significant effect on going concern audit opinions. The previous year's audit opinion as control variable has a significant positive effect so that it can be a control variable.